Persepsi Mahasiswa Pendidikan Bahasa Inggris Tentang Pembelajaran Online Selama Pandemic Covid-19 - Fatimah Azzahrah Zulkfli; Sriati Usman; Abdul Kamaruddin; Mochtar Marhum; Aminah Aminah (Jurnal Kreatif Online, 2023)
This research aims to find out and analyze English education students’ perceptions towards online learning during covid-19 pandemic of the second-years undergraduate students of English Education study program at Tadulako University Palu.  This study applied descriptive qualitative research design. The subject of the research was selected using purposive sampling techniques in which 20 students of English Education study program at Tadulako University. Data were collected through questionnaire and documentation. The research found that the students’ perception towards online learning platforms, methodology, and material to be helpful for them during the pandemic. Few of them agreed that they still face many disadvantages using this learning system, their grades are not getting better and few of the students may not have achieved the learning goal by the end of the lecture. These facts are supported by their final score transcription. The result of the data showed that 73% English Education students agree with the statement that the learning through online learning is helpful. The researcher expected that the result of the study could be beneficial for the undergraduate students to use online learning as their learning system.